UNVEILING THE AUTHENTICITY OF ISLAMIC VALUES: THE EVOLUTION AND TRANSFORMATION OF TRADITIONAL VILLAGES - Eko Nursanty; Astari Wulandari (Journal of Islamic Architecture, 2023)
This paper explores the evolution and transformation of traditional Muslim villages, shedding light on the changes that have occurred over time. Focusing on various traditional Muslim villages, the research employs a multi-faceted approach, combining literature study, historical analysis, field observations, and interviews with community members. Through an extensive review of relevant scholarly works and publications, the study establishes a solid foundation of knowledge and understanding regarding the topic. Field observations and interviews provide firsthand insights into individuals' experiences and perspectives within traditional Muslim villages. The research reveals that traditional Muslim villages have undergone significant transformations in architecture, social structures, and cultural practices. While certain core elements and values have persisted, such as communal harmony and Islamic traditions, these villages have had notable shifts in the physical layout, economic activities, and social dynamics. By unveiling the authenticity of these transformations, this research aims to provide a comprehensive understanding of the complex interplay between tradition and modernity in shaping the identity and sustainability of traditional Muslim villages. The findings of this study, supported by a robust literature study and case studies, can contribute to informed preservation strategies and community development initiatives that honor the heritage while embracing the challenges and opportunities of the contemporary world.